Heritability and genetic association of social organization traits with feeding behavior, feed efficiency and growth in Bos indicus - Valente, Júlia de Paula Soares; De-Sousa, Karolini Tenffen; Deniz, Matheus [UNESP]; Bonilha, Sarah Figueiredo Martins; Mercadante, Maria Eugênia Zerlotti [UNESP]; Dias, Laila Talarico (Elsevier, 2023)
Dominance relationships are important to maintain a stable social organization in group living animals and reduces conflicts between individuals. However, there is a lack of knowledge on the genetic components of social organization. The aim of this study was to estimate the heritability of social organization traits obtained using electronic feed bunk data and their genetic and phenotypic correlations with feeding behavior, feed efficiency and growth in Nellore cattle. Data were obtained from 970 young bulls evaluated in 12 feed efficiency tests. The method used to evaluate social organization was based on feeding event data to detect displacements at the feed bunks. Social organization was evaluated using two traits: dominance value (DV) and social hierarchy (SH). The (co)variance components were estimated by the restricted maximum likelihood method using an animal model in single- and two-traits analyses. The heritability estimates for DV and SH were 0.23 ± 0.07 and 0.25 ± 0.08, respectively. The genetic correlations of the social organization traits with dry matter intake per visit (DV: −0.37 ± 0.17; SH: −0.29 ± 0.17) and time spent at the feed bunk per visit (DV: −0.47 ± 0.16; SH: −0.46 ± 0.15) were negative and ranged from moderate to high, while the genetic correlations with the frequency of feed bunk visits were moderate and positive (DV: 0.34 ± 0.18; SH: 0.22 ± 0.19). On the other hand, the genetic correlations between social organization and growth traits were close to zero. The results indicate that the visits of dominant animals to the feed bunk are shorter but more frequent throughout the day; and these animals tend to consume less feed per visit than subordinate animals. Furthermore, the genetic correlations of DV and SH with growth traits close to zero suggest that selection for higher growth does not affect the social position that the animal occupies within the group. The social organization traits are inheritable and are genetically associated with feeding behavior traits. There is evidence that DV and SH are not genetically correlated with growth traits.
Keywords: Beef cattle; Dominance value; Genetic parameters; Social behavior; Social hierarchy